IMPLEMENTASI MIDEC TERHADAP PROGRAM CAPACITY BUILDING SEKTOR INDUSTRI ELEKTRONIK INDONESIA PADA KERANGKA KERJASAMA IJEPA PERIODE 2008-2013 - Nurul Padzriyah (2021)
The Manufacturing Industry Development Economic Center (MIDEC) is a form of capacity building cooperation provided by the Japanese to the Indonesian side in helping to improve the competitiveness of the Indonesian manufacturing industry. The MIDEC project itself is part of the Indonesia-Japan Economic Partnership Agreement (IJEPA) bilateral cooperation. The collaboration which is based on Presidential Regulation No. 36 of 2008 concerning the "Agreement Between the Republic of Indonesia and Japan for an Economic Partnership" and based on the Minister of Industry Regulation No: 77/M-IND/PER/9/2007 is tasked with carring out bilateral economic cooperation in the development of the manufacturing industry as well as coordinating planning, implementation, monitoring and evaluation. MIDEC covers 13 manufacturing industry sectors, one of which is the electronics sector. The electronics sector within the MIDEC-IJEPA framework gets a programs, such as Technical Assistance/Dispatching Experts and Training. The approach method used in this research is a qualitative approach with the type of case study. This study will answer the research question of how the MIDEC-IJEPA capacity building program in the electronic sector is implemented, because the electronic sector is one of the main driving sectors of the Indonesian economy which has a fairly high weakness in the field of human resources and facilities, but in the implementation process, the program is not optimal already approved. At the beginning of the discussion, this research will discuss the background of the formation of MIDEC which was born from IJEPA, then explain the programs in the electronics sector and the implementation of the capacity building program. Keywords: Bilateral Cooperation, IJEPA, MIDEC, Electronics, Capacity Building